1973
DOI: 10.1017/s002217240004660x
|View full text |Cite
|
Sign up to set email alerts
|

Nasal immunoglobulin responses in acute rubella determined by the immunofluorescent technique

Abstract: SUMMARYThe indirect immunofluorescent technique has been used to study the specific immunoglobulin responses in nasal secretions from ten adults with acute rubella. Titres of IgA antibody in nasal washings usually exceeded those of IgG, but both types of antibody were detected in all patients. They appeared a few days after the rash, reached maximum titres during the second week and then declined. IgA antibody was no longer detectable after 47 days and was not detected at all in nasal washings from adults who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Six patients with rheumatoid factor, which is an IgM antiglobulin, and so can give false positive results by other techniques (Fraser, Shirodaria & Stanford, 1971;Cradock-Watson et al 1972), showed no specific IgM by the present technique, although all had rubella antibodies. Desmyter (1972) likewise showed no false positive results with rheumatoid sera on sucrose gradients.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Six patients with rheumatoid factor, which is an IgM antiglobulin, and so can give false positive results by other techniques (Fraser, Shirodaria & Stanford, 1971;Cradock-Watson et al 1972), showed no specific IgM by the present technique, although all had rubella antibodies. Desmyter (1972) likewise showed no false positive results with rheumatoid sera on sucrose gradients.…”
Section: Discussionmentioning
confidence: 57%
“…Since IgA is also found early after an infection, some workers have suggested that the detection of rubella-specific IgA would also help in these patients (Biurgin-Wolff et al 1971;Cradock-Watson et al 1972). By the present technique, IgA could not be separated from IgG.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…In the UK clinical epidemics are confirmed by an increase in laboratory reports of infection, although these represent only a fraction of the total cases. On the other hand, a serological study in the UK in 1973 [4] confirmed rubella infection in only about half the clinically diagnosed cases. Thus serological confirmation is essential to establish both past and present rubella infection.…”
Section: Recognition Of Rubella Outbreaksmentioning
confidence: 99%